Avaliação do consumo de bactérias pelo zooplâncton em um reservatório eutrófico raso (Reservatório do Monjolinho São Carlos SP) - Hisatugo, Karina Ferreira (Universidade Federal de São Carlos, 2012)
Bacteria, found in terrestrial and aquatic environments, besides their important role in organic matter decomposition and nutrient cycling, are a food source for organisms of the higher trophic levels in the food chain, such as protozooplanktonic and metazooplanktonic organisms. This study aimed to evaluate the relative importance of protozooplanktonic (ciliates and heterotrophic nanoflagellates) and metazooplanktonic organisms (rotifers, cladocerans and copepods) as bacterial consumers throughout a year, which included a rainy and a dry season, in a eutrophic environment (Monjolinho reservoir-SP) by quantifying their ingestion rates. For this purpose, grazing experiments were carried out bimonthly during one year at the sub-surface of a central station of the reservoir using fluorescently labeled bacteria (FLB) dyed with DTAF. In each survey, besides the experiments, limnological (pH, dissolved oxygen, temperature, conductivity, water transparency and nutrients) and biological (chlorophyll-a and phaeophytin concentrations, bacterioplankton, protozooplankton and metazooplankton density) water parameters were also sampled. The heterotrophic nanoflagellates (HNF) showed higher population ingestion rates than the ciliates in dry and rainy seasons, and the HNF smaller than 5μm were the main consumers of bacteria. Among the metazooplanktonic organisms, the rotifers dominated the bacterial ingestion, and the organisms belonging to the genus Filinia and Keratella and to the families Testudinellidae and Brachionidae were the main bacterial consumers. Besides ingesting bacteria, however, protozoa and rotifers population also seemed to be controlled by cladocerans and copepods predation, which, in turn, seemed to be regulated by predation of larger organisms, such as small vertebrates. Thus, the predation control (top-down) occured both on bacterial communities and protozooplanktonic and metazooplanktnic communities and bacteria were regulated both by direct and indirect predation of zooplanktonic population. The resources control (bottom-up) semmed to be higher during the dry season, while in the rainy season bacterial communities were more controlled by predation. The greatest impact on bacterial communities was caused by HNF and ciliates during the rainy season and by HNF and rotifers during the dry one.
Keywords: Ecologia aquática; Bacterivoria; Protozoário; Ciliado; Flagelados; Zooplâncton; Metazooplâncton; Rede Trófica; Bacterivory; Protozoa; Ciliates; Flagellates; Metazooplankton; Trophic Web; CIENCIAS BIOLOGICAS::ECOLOGIA